Long‐term effects of metformin on endothelial function in type 2 diabetes: a randomized controlled trial. (16th September 2013) - de, J.; Kooy, A.; Schalkwijk, C.; van der, J.; Lehert, P.; Bets, D.; Wulffelé, M. G.; Donker, A. J.; Stehouwer, C. D. A.
Abstract Objectives We investigated whether metformin can improve endothelial function and decrease inflammatory activity, and thereby decrease the risk of atherothrombotic disease. Subjects and design A randomized, placebo‐controlled trial with a follow‐up period of 4.3 years set in the outpatient clinics of three nonacademic hospitals (Hoogeveen, Meppel and Coevorden Hospitals, the Netherlands). A total of 390 patients with type 2 diabetes treated with insulin were included. Either metformin 850 mg or placebo (one to three times daily) was added to insulin therapy. Urinary albumin excretion and plasma levels of von Willebrand factor (vWf), soluble vascular adhesion molecule‐1 (sVCAM‐1), soluble E‐selectin (sE‐selectin), tissue‐type plasminogen activator (t‐PA), plasminogen activator inhibitor‐1 (PAI‐1), C‐reactive protein (CRP) and soluble intercellular adhesion molecule‐1 (sICAM‐1) were measured at baseline and after 4, 17, 30, 43 and 52 months. Results Metformin significantly reduced levels of vWF, sVCAM‐1, t‐PA, PAI‐1, CRP and sICAM‐1, which, except for CRP, remained significant after adjustment for baseline differences in age, sex, smoking and severity of previous cardiovascular (CV) disease. No effects on urinary albumin excretion or sE‐selectin were observed. The improvements in vWf and sVCAM‐1 statistically explained about 34% of the reduction in the risk of CV morbidity and mortality associated with metformin treatment in this study. Conclusions Metformin is associated with improvement in some (vWF and sVCAM‐1) but not all markers of endothelial function, which may explain why it is associated with a decreased risk of CV disease in type 2 diabetes.